Rapid Intensification of Hurricane Ian in Relation to Anomalously Warm Subsurface Water on the Wide Continental Shelf - Yonggang Liu; Robert H. Weisberg; Luis Sorinas; Jason A. Law; Alexander K. Nickerson (Geophysical Research Letters)
Abstract Hurricane Ian rapidly intensified from Category 3 to 5 as it transited the wide West Florida Shelf (WFS). This is ascribed to heating by the anomalously warm shelf waters, despite the water depth being shallow when compared to the thicker, mixed layer areas of the deeper ocean. By examining temperature from long‐term moorings, we found that the sea surface and subsurface temperatures exceeded the climatologies by 1–2°C and 2–3°C, respectively. Additionally, these anomalously high temperatures in summer/fall of 2022 were related to the absence of Gulf of Mexico Loop Current interactions with the WFS slope at its “pressure point”. Without such offshore forcing to induce an upwelling circulation, the warmer waters on the shelf were not flushed and replaced by colder waters of deeper ocean origin. This work highlights the importance of subsurface temperature and ocean circulation monitoring on shallow continental shelves, which are largely overlooked in hurricane‐related ocean heat content observational programs.